Effect of Acacia Polyphenol Supplementation on Exercise-Induced Oxidative Stress in Mice Liver and Skeletal Muscle - Koichi Yada; Llion Arwyn Roberts; Natsumi Oginome; Katsuhiko Suzuki (MDPI AG, 2019)
The purpose of this study was to investigate the effects of acacia polyphenol (AP) supplementation on exercise-induced oxidative stress in mouse liver and skeletal muscle. Plasma aspartate aminotransferase (AST), liver and skeletal muscle levels of thiobarbituric acid reactive substance (TBARS), and levels of skeletal muscle protein carbonyls increased immediately after exhaustive exercise. Exhaustive exercise also decreased liver glutathione (GSH). These results suggest that the exhaustive exercise used in this study induced tissue damage and oxidative stress. Contrary to our expectations, AP supplementation increased plasma AST and alanine aminotransferase activities, liver levels of TBARS, and protein carbonyls. Furthermore, AP supplementation decreased glutathione and glutathione peroxidase activity in the liver. On the other hand, AP supplementation decreased TBARS levels in skeletal muscle. These results suggest that oral high-dose AP administration decreased oxidative stress in skeletal muscle but induced oxidative stress in the liver and increased hepatotoxicity.